Evaluation of Toxicity and Repellency of Essential Oils of Family Rutaceae Against Black Ants (Lasius niger) in Pakistan - Mehmood, Ferhat; Manzoor, Farkhanda; ud Din Khan, Zaheer; Imran Ali, Mahwish; Khan, Islamullah; Muhammad Akmal Rahim, Syed (Asian Journal of Chemistry, 2012)
A study was conducted to evaluate the toxicity and repellency of essential oils from leaves of Skimmia laureola (DC.), Murraya paniculata (Linn) cv. Desi, Murraya paniculata (Linn) cv. China and Murraya koenigii (Linn.) of family Rutaceae in Pakistan. The oils were tested at three concentrations i.e. 1, 5 and 10 %. Common ant species Lasius niger (black ant) of Pakistan were selected and subjected to force-feeding at room temperature. Results showed that insecticidal activity of each tested essential oil was significantly different from each other. Murraya paniculata (both varieties) was the most effective tested oil (LC50 = 6.58 μL) while Skimmia laureolas showed least repellent activity (LC50 = 10.15 μL).